Internal Genetic Structure and Outcrossing Rate in a Natural Population of Araucaria angustifolia (Bert.) O. Kuntze - Mantovani, Adelar; Morellato, L. Patrícia C; Reis, Maurício S. dos (The Journal of heredity, 2006)
The internal genetic structure and outcrossing rate of a population of Araucaria angustifolia (Bert.) O. Kuntze were investigated using 16 allozyme loci. Estimates of the mean number of alleles per loci (1.6), percentage of polymorphic loci (43.8%), and expected genetic diversity (0.170) were similar to those obtained for other gymnosperms. The analysis of spatial autocorrelation demonstrated the presence of internal structure in the first distance classes (up to 70 m), suggesting the presence of family structure. The outcrossing rate was high (0.956), as expected for a dioecious species. However, it was different from unity, indicating outcrossings between related individuals and corroborating the presence of internal genetic structure. The results of this study have implications for the methodologies used in conservation collections and for the use or analysis of this forest species.